Main trends and directions of development of the Russian printing services market - O. V. Babich; M. I. Tyulyagina (Путеводитель предпринимателя, 2020)
The subject of the research is the problems of improving the efficiency of the printing services market. The article describes the current problems of the development of the market of printing services, the main directions of development of the printing services market in Russia and abroad are presented.